Mixed method Analysis on Dream of Smart Urbanism - Al-Mansouri, Ahmad; El-Din Abdallah, Nour; Hassanein, Leila (TOPAZART, 2025)
The rapid pace of global urbanization has intensified the need for innovative solutions that enhance the livability, sustainability, and governance of cities. This study investigates the evolving landscape of smart urbanism by exploring how digital technologies—such as IoT, AI, and big data—are integrated into urban systems to address growing challenges. Adopting a mixed-method research design, the study combines quantitative surveys and qualitative interviews across global smart cities to capture citizen perceptions, technological impacts, and governance implications. NVivo software is employed for thematic analysis of qualitative data, revealing dominant themes such as convenience, digital access, mobility, and trust in technology. Findings highlight both the opportunities and challenges of smart urbanism, including issues of digital inclusion, data security, and institutional readiness. The study offers practical insights for policymakers, urban planners, and technologists aiming to implement citizen-centric, inclusive, and sustainable smart city strategies.